2006
DOI: 10.1111/j.1469-1809.2005.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Factors and Gender on the Heritability of Bone Mineral Density and Bone Size

Abstract: SummaryBone mineral density (BMD), a risk factor for osteoporosis, is believed to be under genetic control. The effect of environmental factors and gender on the heritability of BMD and bone size is ill-defined. In this study, heritability estimates (h 2 ) were determined in 3,320 southern Chinese subjects from 1,019 families using the variance components model. The h 2 for age, weight and height-adjusted BMD was 0.63-0.71 for females, and 0.74-0.79 for males; and for bone size, 0.44-0.64 for females and 0.32-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
1
2

Year Published

2008
2008
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 35 publications
0
32
1
2
Order By: Relevance
“…We found that in females, percentage of variation explained by all the covariates was much higher than in males. Similarly, in a study of 3,320 Chinese subjects from 1,019 families (Ng et al, 2006), age, weight, height, as well as intake of isoflavones and calcium, physical activity, smoking, drinking, contributed from only 13% to 31% among men; for women, addition of age at menarche and menopause resulted in 32% to 46% of explained total variance in BMD. Similar results were reported in the Framingham families (R 2 from 8% to 20% in men but 19% to 41% in women (Karasik et al, 2002)) and in the Amish families (Brown et al, 2004).…”
Section: Gender-specific Heritability Of Bmd: Human Studiesmentioning
confidence: 95%
“…We found that in females, percentage of variation explained by all the covariates was much higher than in males. Similarly, in a study of 3,320 Chinese subjects from 1,019 families (Ng et al, 2006), age, weight, height, as well as intake of isoflavones and calcium, physical activity, smoking, drinking, contributed from only 13% to 31% among men; for women, addition of age at menarche and menopause resulted in 32% to 46% of explained total variance in BMD. Similar results were reported in the Framingham families (R 2 from 8% to 20% in men but 19% to 41% in women (Karasik et al, 2002)) and in the Amish families (Brown et al, 2004).…”
Section: Gender-specific Heritability Of Bmd: Human Studiesmentioning
confidence: 95%
“…In fact part of the effects described in the participants of different sports may have been caused by selection bias. Girls or boys with a larger musculoskeletal size and bone mass, [110] due to inherited characteristics, may choose to exercise because they may be more likely to be successful in competition and feel more rewarded by exercise practice. To rule out such a possibility, longitudinal studies and randomized clinical control trials are necessary.…”
Section: Young Womenmentioning
confidence: 99%
“…6 Environmental factors also affect the risk for future fracture and include physical activity, calcium intake, smoking, and possibly alcohol intake. [6][7][8][9][10] While some studies have found site-specific gender differences in BMD heritability, others have observed no gender differences. 2 Many of these studies were limited in their site selection, often focusing mostly on BMD of the hip, spine, femoral neck and forearm, and only one 11 was a twin study.…”
mentioning
confidence: 99%